The role of phytochromes in stress tolerance - Carvalho, R. F. [UNESP]; Campos, M. L.; Azevedo, R. A. (Springer Nature, 2013)
Phytochromes, which absorb red (R)/far red (FR) light, are the most characterized photoreceptors in plants and have been shown to mediate a wide range of molecular and biochemical responses. These include responses to biotic and abiotic stresses, which are currently a major challenge in plant research. Extensive studies exploring the molecular and biochemical basis by which phytochromes modulate stresses such as drought, high light, high and low temperatures or herbivory, among other, have been carried out in many plant species. In particular, considerable efforts have also been made to unravel the involvement of phytochromes in salt stress responses. For example, many of the stress responses involving phytochrome are now understood following studies using R/FR light ratio treatments, as well as the isolation and characterization of photomorphogenic mutants and transgenic plants, which have revealed an important role of phytochromes on salt stress tolerance mechanisms. In this chapter, we will explore pieces of information available to make clear the perspectives focused on photomorphogenesis manipulation in the scope of agriculture.
Keywords: Abiotic stress; Biotic stress; Photoreceptors; Phytochromes; Stress modulation